Integrasi Kearifan Lokal dalam Model Pembelajaran PAUD di Tenggarong - Masdiana Maula; Lina Revilla Malik (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to describe the integration of local wisdom of Kutai culture in the learning model in Early Childhood Education, especially in kindergarten 02 Tenggarong. Using a descriptive qualitative approach, this study explores the application of Kutai cultural values in learning activities to strengthen children's cultural identity, character, and understanding of local cultural heritage. The focus of the research includes the implementation and challenges faced by teachers in integrating Kutai culture into the PAUD curriculum. Data collection is carried out through interviews, observations, and documentation by involving teachers and principals as the main informants. The data analysis technique uses a four-stage model, namely data collection, data condensation, data presentation, and conclusion drawn. The results of the study showed that the integration of local wisdom was carried out through various activities, such as the introduction of the jepen dance, the introduction of Erau traditional ceremonies, making dragon replicas, ornaments of hornbill hats, beseprah traditions, visits to the Mulawarman Museum, the introduction of cakes and traditional games in the learning process. This strategy not only improves children's understanding of local culture but also strengthens the skills of cognitive, motor, and social-emotional aspects in children. The main challenge in this implementation is the lack of structured references or guidelines regarding local culture-based learning, but it can be overcome with collaboration between schools and the community